Dampak Perilaku Bullying terhadap Peserta Didik pada Jenjang Sekolah Dasar - Nopriyanti, Humaira; Khasanah, Lailatul; Sholeha, Maratus; Saputra, Rizki Aprian; Meisya, Syahdira (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Education at the elementary school level should carried out within a school scope and environment that provides a sense of security, calm and fun for each student. Various things that can cause the scope of learning in elementary school to be less enjoyable and feel unsafe are due to bullying towards students. The main aim of this research is to see what impacts bullying behavior has on students. The research show that the impact of bullying behavior covers a fairly broad impact. The impact of bullying is on both the perpetrator of the bullying and the victim of the bullying. Victims of bullying experience feelings of inferiority, difficulty in social relationships and experience a decline in learning outcomes and there are also students whose self-confidence decreases and is afraid when meeting other people. For the perpetrator of bullying, the perpetrator becomes a person not have empathy and can become arrogant towards friends or other people if it is not addressed immediately; (2) the factors that cause bullying consist of various factors including: family, peer and environmental factors as well as gadget factors.